Analysis of Public Service Innovation from Competition at the Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia in 2020-2023 - Ariza Putri, Ismi Despi; Noviaristanti, Siska (Eastasouth Institute, 2025)
Public service innovation is the government's main focus in an effort to make it easier for the public to access information, especially through digital transformation that can provide benefits for both the public and the government itself. The Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia (Ministry of PANRB) plays a role as a leading sector in encouraging the realization of public service innovation, one of which is through holding an annual competition that aims to motivate ministries, institutions, local governments, BUMN, and BUMD to continue to create service innovations. This study aims to identify various forms of public service innovation in Indonesia based on type, results, policy sectors, and geographical location, as well as to provide theoretical contributions and practical benefits for optimizing equitable public services. Using qualitative methods with data collection techniques through document archives from the 2020–2023 public service innovation competition, the study found that district governments are the dominant actors, while BUMN participation is still low, with innovation concentrated in Java and dominated by the public service, health, and governance sectors. Although technology and social innovations are growing rapidly, aspects of governance and inclusion are still lacking, so it is recommended to strengthen regional capacity, increase BUMN participation, improve innovation replication, and integrate social dimensions. Further research needs to focus on evaluating impacts, regional disparities, and internal organizational factors to strengthen the effectiveness of public service innovation as a whole.